Comparação entre testes bioquímicos e análise da sequência parcial do gene HSP60 para a identificação de isolados de Streptococcus equi - Silva, Mariana Sá e (2005)
Streptococcus equi is the etiological agent of strangles. Opportunistic agents from the same group are frequently isolated from horses with strangles and may induce mistake diagnostic. Among the subspecies of S. equi the phenotypic characteristics are almost undistinguishable; however the pathogenic potential is widely differentiated. The objective of this study was to determine the phenotypic and molecular characteristics of S. equi isolates obtained from samples of clinical cases of strangles by sequencing the hsp60 gene. By phenotypical assays 26 strains of Streptococcus sp. were identified, 18 were characterized as S. equi subsp. equi, five as S. equi subsp. zooepidemicus, two as S. dysgalactiae subsp., equisimilis, and one as Streptococcus sp.; However using molecular characterization, 21 isolates were identified as S. equi subsp. equi and five as S. equi subsp. zooepidemicus. The analysis of the hsp60 sequence is a good discriminatory tool and can be useful as a method of differentiation, principally for the characterization of atypical isolates